2014
DOI: 10.1039/c4cc03309d
|View full text |Cite
|
Sign up to set email alerts
|

(Electro)catalytic C–C bond formation reaction with a redox-active cobalt complex

Abstract: Cooperativity between cobalt and non-innocent ligands in electron transfer processes has been utilized for (electro)catalytic C-C bond formation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…The catalytic current in all cases was measured at -1.0 V. This gives an overall rate law for the R F I catalytic reduction rate=k[R F I] 2 [(bpy)Fe(III)] 2 ]. [61][62][63][64][65][66][67][68][69] Figure S7 confirms, that the order of the reaction with respect to substrate 20 (R F I) twice as much as the reaction order in catalyst [(bpy)Fe]. Possibly, this result shows that two moles of substrate (R F I) is necessary for each mole of iron dimer.…”
Section: Cyclic Voltammetrymentioning
confidence: 64%
See 1 more Smart Citation
“…The catalytic current in all cases was measured at -1.0 V. This gives an overall rate law for the R F I catalytic reduction rate=k[R F I] 2 [(bpy)Fe(III)] 2 ]. [61][62][63][64][65][66][67][68][69] Figure S7 confirms, that the order of the reaction with respect to substrate 20 (R F I) twice as much as the reaction order in catalyst [(bpy)Fe]. Possibly, this result shows that two moles of substrate (R F I) is necessary for each mole of iron dimer.…”
Section: Cyclic Voltammetrymentioning
confidence: 64%
“…homogeneous catalytic processes electrochemically induced and applied previously in numerous publications. [61][62][63][64][65][66][67][68][69] A plot catalytic current enhancement in the R F I presence vs. substrate (R F I) concentration shows linear dependence indicating the rate of reaction is second order with respect to the perfluoroalkyl 5 substrate (Fig.8). 61 (Fig.9).…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…The cobalt complex 17 involving diiminosemiquinone ligand electrocatalyzes the coupling reaction of benzyl bromide to form 1,2-diphenylethane ( Figure 5). [20] Motivation to investigate the electrocatalytic C-C coupling reactivity of 17 arose when its cyclic voltammetric response displayed a catalytic current at the potential of second reduction. Similar observation however was absent when the same response was measured in THF, thereby, delivering insights into C-Cl activation being responsible for the catalytic current by the ligand centered two electron reduced [Co(L 2-) 2 ] 2species.…”
Section: Eurjicmentioning
confidence: 99%
“…Generation of a redox‐active cobalt (electro)catalyst has been described by the Sarkar group, and has been applied to a Csp 3 −Csp 3 homocoupling reaction (Scheme ) . Electrochemical studies in CH 2 Cl 2 showed that the cobalt (II) complex 30 , with its two diiminosemiquinone ligands, was able to support a first reversible reduction wave at −1.47 V vs. Fc + /Fc, whereas a catalytic current was observed for the second reduction wave.…”
Section: Csp3−csp3 Couplingmentioning
confidence: 99%